The Adoption and Effect of Artificial Intelligence on Human Resources Management - Tyagi, Pallavi (Emerald Publishing Limited, 2023)
Emerald Studies In Finance, Insurance, And Risk Management 7Bexplores how AI and Automation enhance the basic functions of human resource management
Description based on publisher supplied metadata and other sources
Keywords: Artificial intelligence; Digitalisierung; Künstliche Intelligenz; Personalwesen; Humanvermögen; Personalentwicklung; Aufsatzsammlung